CHEMISTRY AND PHARMACOLOGY OF SYRINGIN, A NOVEL BIOGLYCOSIDE: A REVIEW - Rao Us, Mahadeva; Zin, Thant; Abdurrazak, Muhammad; Ado Ahmad, Bashir (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Syringin, a phenylpropanoid glycoside belongs to eleutheroside derivative. This bioactive compound was identified in several plants including Musa paradisiaca, Jasminum mesnyi, Edgeworthia chrysantha, Acanthopanax senticosus, etc. According to Nair et al., syringin is synthesized from the precursor phenylalanine by a series of reactions. Zhao has described a rapid extraction method based on the ultrasound-assisted extraction of syringin from the bark of Ilex rotunda thumb using response surface methodology. Based on the findings made by Jizhong et al., the bioactive compound syringin was separated from the n-butanol extract of the stems and barks of E. chrysantha Lindl by high-speed counter-current chromatography. According to Choi et al., the enrichment and purification of syringin from A. senticosus was performed based on the adsorption and desorption properties of commercial macroporous resins. The pharmacological properties of syringin includes scavenging the free radicals, protection against neuronal cell damage, inhibition of apoptosis, anti-diabetic effect, anti-inflammatory potential, anti-nociceptive action, anti-allergic effect, etc. Keywords: Phenylpropanoid glycoside, Eleutheroside, Apoptosis, Nociceptive.